2017
DOI: 10.1016/j.eats.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Medial Meniscus Posterior Root Tear Repair Using a 2-Simple-Suture Pullout Technique

Abstract: Medial meniscus posterior root tear is one of the underestimated knee injuries in terms of incidence. Despite its grave sequelae, using simple but effective technique can maintain the native knee joint longevity. In the current note, a 2-simple-suture pullout technique was used to effectively reduce the meniscus posterior root to its anatomic position. The success of the technique depended on proper tool selection as well as tibial tunnel direction that allowed easier root suturing and better suture tensioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These sutures are pulled through and secured to the tibial tunnel. [60][61][62] Potential complications of meniscal resection or repair include general issues related to the surgery itself such as infection, persistent portal drainage, and neurovascular injury. Articular cartilage damage is a potential complication with both meniscal repair techniques and meniscal resection, particularly excessive resection.…”
Section: Operative Goals and Optionsmentioning
confidence: 99%
“…These sutures are pulled through and secured to the tibial tunnel. [60][61][62] Potential complications of meniscal resection or repair include general issues related to the surgery itself such as infection, persistent portal drainage, and neurovascular injury. Articular cartilage damage is a potential complication with both meniscal repair techniques and meniscal resection, particularly excessive resection.…”
Section: Operative Goals and Optionsmentioning
confidence: 99%
“…Furthermore, studies have found that poor prognostic factors after PMMR tears repair are modified outerbridge classification grade ≥3, chondral lesions, varus alignment >5°, older age, female sex, high BMI and medial meniscus extrusion [ 8 , 16 ]. To improve the poor prognosis of PMMR tears repair, studies on transtibial pull-out fixation have focused on the meniscus–suture interface using different fixation techniques, such as the modified Mason–Allen technique or two simple sutures [ 17 , 18 ]. However, to date, few studies have examined tibial fixation methods in PMMR repair.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 13 , 14 , 15 , 16 Other authors have advocated different suture configurations and types with a pullout technique to improve stability and prevent excursion although mainly in biomechanical studies. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 …”
mentioning
confidence: 99%
“…5,[13][14][15][16] Other authors have advocated different suture configurations and types with a pullout technique to improve stability and prevent excursion although mainly in biomechanical studies. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Many authors have attempted to decrease extrusion and improve function through alternate suture techniques, using more sutures, additional anchors, or fixation of the posteromedial tibial plateau. We believe that by combining the clinical and biomechanical evidence with the basic science and anatomic constraints of the medial meniscus while attempting to address the meniscal root pathology, we can achieve a safe, reproducible, and biomechanically sound repair of MMPRTs.…”
mentioning
confidence: 99%